OpenStudy (ajprincess):

plzz help. How do I prove p∧(pvq)=p using laws of algebra of propositions

6 years ago
OpenStudy (jamesj):

Do you have this theorem? Let A(x) be a statement involving x. If ~x ^ A(x) is always false, then A(x) = x. If so, then notice ~p ^ p ^ (pvq) = FALSE, hence p ^ (pvq) = p. Another way is ....

6 years ago
OpenStudy (jamesj):

p∧(pvq) = (p^p) v (p^q) = p v (p ^ q), because p^p = p = p , because if p is false then both p and p^q are false.

6 years ago
OpenStudy (anonymous):

pvq would have to be = 1

6 years ago
OpenStudy (anonymous):

1/vq=p

6 years ago
OpenStudy (anonymous):

1/vq=p ^ that is not a :P

6 years ago
OpenStudy (ajprincess):

Thanxxx a lott.

6 years ago
Similar Questions: